Networking in the Plant Microbiome - van der Heijden, Marcel G. A.; Hartmann, Martin (PLOS Biology, 2016)
This Primer assesses recent evidence that the microbiome of plants contains microbial networks and keystone species that influence plant health and ecosystem functioning. Read the accompanying Research Article.